EFEKTIVITAS MODEL PEMBELAJARAN MAKE A MATCH TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Iis Sumaesih; Pramudiyanti Pramudiyanti; Arwin Achmad (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
This experiment was aim to find effectiveness Make A Match model of learning activities and outcomes of students. The research design was non equivalent pretest – posttest.  The research sample were students in Xb and Xc class that was selected by cluster random sampling method. This research data the form of quantitative which obtained from the average value of test were analyzed by using t-test and U-test and the qualitative data which obtained form the observation sheet of learning activities and questionnaire responses of students were analyzed descriptive. The results showed that the average of students outcomes in experimental class are higher than control (experiment= 77.2; control = 71.1). The average of student learning activities percentage in all observed aspects in experimental class shown higher enhancement than control (experiment = 83.6; control = 63.6). The students also gives positive responses to applicating cooperative learning model type Make A Match.Penelitian ini bertujuan mengetahui efektivitas model Make A Match terhadap aktivitas dan hasil belajar siswa. Desain penelitian pretes-postes tak ekuivalen. Sampel penelitian siswa kelas Xb dan Xc dipilih menggunakan metode cluster random sampling. Data penelitian berupa data kuantitatif diperoleh dari rata-rata nilai tes dianalisis menggunakan uji-t dan uji-U dan data kualitatif diperoleh dari lembar observasi aktivitas belajar dan angket tanggapan siswa dianalisis secara deskriptif. Hasil penelitian menunjukkan hasil belajar  kelas eksperimen lebih tinggi (eksperimen = 77,2; kontrol = 71,1). Rata-rata persentase aktivitas siswa semua aspek kelas eksperimen juga menunjukkan peningkatan yang lebih tinggi (eksperimen = 83,6; kontrol = 63,6). Semua siswa memberikan tanggapan positif terhadap penggunaan model Make A Match.Kata kunci :  aktivitas belajar, hasil belajar, make a match